2022
DOI: 10.3389/fnut.2022.871346
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on the Function and Purification of Milk Exosomes: A Review

Abstract: Exosomes are nano-scale extracellular vesicles, which can be used as drug carriers, tumor treatment, intestinal development and immune regulator. That is why it has great potential in pharmacy, functional foods, nutritional supplements, especially those for infants, postoperative patients, chemotherapy patients and the elderly. In addition, abnormal exosome level is also related to diseases such as cardiovascular diseases, tumor, diabetes, neurodegenerative and autoimmune diseases, as well as infectious diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 112 publications
1
41
0
Order By: Relevance
“…52 Four transmembrane proteins and membrane-bound proteins distributed on the surface of exosomes can effectively enhance the stability of miRNAs circulating in vivo . 9 Hata et al (2010) showed that compared to synthetic miRNAs and mRNAs, bovine milk miRNAs, and mRNAs could still show good stability under simulated gastric juice low pH environment and RNA enzyme conditions, and their utilization efficiency and quality were not affected. 53 Lopez Hazas et al (2022) similarly demonstrated that miRNAs encapsulated by bovine milk exosomes were more stable than free miRNAs and had better digestive tolerance, prolonging the degradation rate of specific miRNAs in mice.…”
Section: Bioavailability Of Milk-derived Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Four transmembrane proteins and membrane-bound proteins distributed on the surface of exosomes can effectively enhance the stability of miRNAs circulating in vivo . 9 Hata et al (2010) showed that compared to synthetic miRNAs and mRNAs, bovine milk miRNAs, and mRNAs could still show good stability under simulated gastric juice low pH environment and RNA enzyme conditions, and their utilization efficiency and quality were not affected. 53 Lopez Hazas et al (2022) similarly demonstrated that miRNAs encapsulated by bovine milk exosomes were more stable than free miRNAs and had better digestive tolerance, prolonging the degradation rate of specific miRNAs in mice.…”
Section: Bioavailability Of Milk-derived Mirnasmentioning
confidence: 99%
“…As an intercellular communication molecule, milkderived exosomes can play an essential role in regulating signal transduction, immune tolerance, and inflammatory responses by delivering miRNAs they carry across borders to intestinal target cells through the food uptake pathway. [8][9][10] Accordingly, this paper summarizes and composes the research progress on the stability, transport mode, and uptake pattern of milk-derived miRNAs across species, focuses on the possible mechanisms of milk-derived miRNAs to protect the intestinal mucosal barrier, and also analyzes the effects of processing treatment on miRNAs in milk and dairy products to provide a reference for the development and utilization of milk-derived miRNAs in food. process of miRNAs in mammary cells has been initially elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Our results of fluorescent labeling experiment also confirm that HM exosomes can be uptake by cultured HepG2 cells, and also can be absorbed in the intestine of mice and distributed in mice liver, which is in agreement with previous reports. [ 1,37 ] Collectively, our results demonstrate that HM exosomes from GDM and healthy parturient exhibit distinct regulatory bioactivities on hepatocyte proliferation, which is probably because that GDM enriches miR‐101‐3p into HM exosomes, and HM exosomes from GDM parturient deliver miR‐101‐3p to target and downregulate mTOR in both cultured HepG2 cells and mice liver resulting in the inhibition of hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 80%
“…from mothers to breastfeeding infants. [1,7,16,36,37] Maternal health conditions influence the composition of HM exosomes and may further change the functionalities of HM exosomes. Results in this study and others [18] indicate that GDM changes the miRNA profiles in HM exo-somes.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have compared the functional activity of bovine, buffalo, goat, and yak milk-derived exosomes [ 128 , 129 , 130 , 131 ]. As drug delivery vehicles, milk-derived exosomes present many advantages: safety as determined by failure to induce obvious immunogenicity or cytotoxicity [ 132 , 133 , 134 ]; ability to pass through barrier systems, such as the blood-brain barrier [ 135 ]; effective targeting [ 136 ], enhancement of the oral availability of drugs [ 137 ]; high stability against extreme stimuli [ 138 , 139 ]; standardization of cost and preparation processes [ 120 , 140 , 141 ], etc.…”
Section: Application Prospects Of Exosomes As Drug Delivery Vehicles ...mentioning
confidence: 99%